Identification of in vitro effect of 4-octylphenol on the basal and human chorionic gonadotropin (hCG) stimulated secretion of androgens and superoxide radicals in mouse Leydig cells. Issue 8 (3rd July 2019) - Jambor, Tomas; Greifova, Hana; Kovacik, Anton; Kovacikova, Eva; Massanyi, Peter; Forgacs, Zsolt; Lukac, Norbert
Abstract: The aim of our in vitro study was to assess the potential effect of 4-octylphenol (4-OP) on the basal and human chorionic gonadotropin (hCG)-stimulated cholesterol levels and biosynthesis of steroid hormones in cultured mouse Leydig cells. In addition, we evaluated the intracellular superoxide production following 4-OP treatment. Isolated mouse Leydig cells were cultured in the presence or absence of 1 IU/mL (hCG) with the addition of 0.04; 0.2; 1.0; 2.5 and 5.0 µg/mL 4-OP during 44 h. The level of cholesterol was determined from the culture medium using photometry. Quantification of steroid hormones was performed by the enzyme linked immunosorbent assay and intracellular generation of superoxide radicals was assessed by the nitroblue-tetrazolium assay. Administered concentrations of 4-OP (0.04-5.0 µg/mL) did not affect basal and hCG-stimulated cholesterol level significantly. However, basal DHEA secretion was increased significantly (P < 0.001) in the highest experimental dose (5 µg/mL) of 4-OP. By hCG-stimulated DHEA secretion, a significant ( P < 0.001 ) decrease was recorded at 5.0 µg/mL 4-OP in comparison to the control group. The stimulatory effect of 4-OP was also confirmed in androstenedione secretion, when 2.5 and 5.0 µg/mL increased hormone secretion significantly (P˂0.05; P˂0.001) . Exposure to experimental concentrations (0.04 to 5.0 µg/mL) of tested chemical reduced hCG-stimulated androstenedione formation, but not significantly. Measurements of basal testosterone production have shown significant (P˂0.01; P˂0.001) increase at 1.0 ; 2.5 and 5.0 µg/mL of 4-OP. Furthermore, 44 h treatment by 4-OP (1.0-5.0 µg/mL) caused significant ( P˂0.01; P˂0.001 ) intracellular accumulation of superoxide radicals in exposed cells. A considerably more detailed and systematic research is required for a better understanding of risks associated with male reproductive system in humans and wildlife.